Proposal of quality indicators for cardiac rehabilitation after acute coronary syndrome in Japan: a modified Delphi method and practice test. Issue 1 (27th January 2017) - Ohtera, Shosuke; Kanazawa, Natsuko; Ozasa, Neiko; Ueshima, Kenji; Nakayama, Takeo
Abstract : Objectives: Cardiac rehabilitation is underused and its quality in practice is unclear. A quality indicator is a measurable element of clinical practice performance. This study aimed to propose a set of quality indicators for cardiac rehabilitation following an acute coronary event in the Japanese population and conduct a small-size practice test to confirm feasibility and applicability of the indicators in real-world clinical practice. Design and setting: This study used a modified Delphi technique (the RAND/UCLA appropriateness method), a consensus method which involves an evidence review, a face-to-face multidisciplinary panel meeting and repeated anonymous rating. Evidence to be reviewed included clinical practice guidelines available in English or Japanese and existing quality indicators. Performance of each indicator was assessed retrospectively using medical records at a university hospital in Japan. Participants: 10 professionals in cardiac rehabilitation for the consensus panel. Results: In the literature review, 23 clinical practice guidelines and 16 existing indicators were identified to generate potential indicators. Through the consensus-building process, a total of 30 indicators were assessed and finally 13 indicators were accepted. The practice test (n=39) revealed that 74% of patients underwent cardiac rehabilitation. Median performance of process measures was 93% (IQR 46–100%). 'Communication with the doctor who referred the patient to cardiac rehabilitation' and 'continuous participation in cardiac rehabilitation' had low performance (32% and 38%, respectively). Conclusions: A modified Delphi technique identified a comprehensive set of quality indicators for cardiac rehabilitation. The single-site, small-size practice test confirmed that most of the proposed indicators were measurable in real-world clinical practice. However, some clinical processes which are not covered by national health insurance in Japan had low performance. Further studies will be needed to clarify and improve the quality of care in cardiac rehabilitation.